ROLE OPTIMIZATION OF REGIONAL REPRESENTATIVE COUNCIL IN THE LEGISLATIVE FUNCTION - Gunawan, Bambang Panji; Suhartono, Slamet; Mangesti, Yovita Arie; Miarsa, Fajar Rachmad Dwi (jfpublisher, 2023)
The Regional Representative Council or DPD is an institution that represents the region as a state institution. After the bicameral parliamentary structure was established, the idea of bicameral became both strengthened and weakened. This research aims to identify the situation of the Regional Representative Council according to the 1945 Constitutional amendment and the weaknesses of the Regional Representative Council in implementing its legislative function. The type of research used in this legal research is descriptive-analytical with an evaluative normative juridical approach. The findings of the research identified that the situation of the Regional Representative Council, according to the 1945 Constitutional amendment, caused several changes in its position, members, functions, term of office, as well as its relationship with the House of Representatives. On the other hand, the weaknesses of the Regional Representative Council in implementing its legislative function were caused by its’ limited authorities, its’ unequal position with the House of Representatives, and its consideration, which was not even being considered by the House of Representatives as the House of Representatives was not obligated to, its' non-exclusive status, and its’ potentially conflict of interest.